Electronic L1 and L2 glosses’ impact on vocabulary acquisition of Moroccan English as a foreign language learners - BrahiM OutamghartE; Mohamed Yeou; Hicham Zyad (Australian Journal of Applied Linguistics)
With the growing interest in integrating ICT in the EFL classroom, the present study investigates the impact of electronic first language (L1) translations and second language (L2) definitions glosses on incidental vocabulary learning and retention among Moroccan EFL learners. 172 first-year university students participated in this study. The participants were divided into three groups: a control group with no glosses (NGG), and two experimental groups namely L1 electronic gloss (EL1GG) and L2 electronic gloss group (EL2GG). During the eight-week treatment, participants had to read texts without glosses or glossed with target vocabulary items as well as complete reading comprehension questions and vocabulary tests. The results of one-way ANOVA revealed that gloss conditions significantly outperformed the no-gloss condition. Qualitative data from semi-structured interviews provided more information about learners' perceptions and preferences regarding gloss language. The study also emphasizes the importance of considering individual learner differences and providing a choice of gloss type to cater for different learning styles and needs. Implications for researchers and EFL teachers are provided.